2017
DOI: 10.1007/s10658-017-1200-2
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium head blight incidence and detection of Fusarium toxins in wheat in relation to agronomic factors

Abstract: We investigated incidences of Fusarium head blight (FHB) and concentrations of six mycotoxins (deoxynivalenol, nivalenol, 3-acetyldeoxynivalenol, T-2 toxin, HT-2 toxin and zearalenone) in wheat from 2010 to 2013. Field trials were conducted at the Experimental Station of Cultivar Testing in Chrząstowo, Poland (53 o 11'N, 17 o 35'E). We examined the effects of four agronomic factors, including pre-crop type (corn, sugar beets and wheat), date of sowing (late autumn: November 8-December 9 or spring: March 29-Apr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 65 publications
2
15
0
Order By: Relevance
“…The impact of temperature was not evaluated because the average temperatures in the crucial period of ear infection were similar throughout all investigation years and did not exceed 17-19°C. The present investigation showed that F. avenaceum was the dominant species, which agrees with several other findings [25][26][27]. Similarly, a high occurrence of F. poae was detected in our research, which also supports the data in the literature [22,28].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The impact of temperature was not evaluated because the average temperatures in the crucial period of ear infection were similar throughout all investigation years and did not exceed 17-19°C. The present investigation showed that F. avenaceum was the dominant species, which agrees with several other findings [25][26][27]. Similarly, a high occurrence of F. poae was detected in our research, which also supports the data in the literature [22,28].…”
Section: Discussionsupporting
confidence: 93%
“…The importance of crop rotation was highlighted by Wenda-Piesik et al [27], where an increasing proportion of Fusarium spp. was detected in wheat grains after the precropping of wheat and maize.…”
Section: Discussionmentioning
confidence: 99%
“…This was probably due to differences in rain fallen in the 2 years considered; in fact, Fusarium Head Blight (FHB) is strongly dependent on specific weather condition (Doohan et al, 2003), mainly rainfall and temperature. A previous study underlined that a monthly rainfall sum of 113.9 mm and a monthly average temperature of 15.5°C are the best conditions for FHB occurrence (Wenda-Piesik et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Delaying optimal sowing date by 20-25 days increased Fusarium disease index under central European conditions in both susceptible and tolerant winter wheat cultivars, whereas increasing sowing density from 400 to 600 germinated seeds/m 2 did not show differences (Gorczyca et al 2018). However, in cultivars that do not need vernalization, a delay in sowing dates to late autumn or early spring did not have an effect on Fusarium disease index or DON contamination (Wenda-Piesik et al 2017).…”
Section: Agricultural Practicesmentioning
confidence: 81%
“…The values vary widely between 10% and 50%, depending on the weather conditions and Fusarium populations (Kikot et al 2011;Xu and Nicholson 2009). Likewise, it has been shown that agricultural practices such as crop rotation, tillage, sowing date, fungicide treatment, cultivar, fertilizer source, irrigation regimes and overall production system (conventional vs organic) have an influence on the final DON concentration in both wheat and barley (Bernhoft et al 2012;Wenda-Piesik et al 2017). In the case of FCR, yield reductions can reach up to 26% in Australia and 50% in the USA (Liu and Ogbonnaya 2015).…”
Section: Yield and Quality Lossesmentioning
confidence: 99%